UP DocuTrak an assessment of an in-house developed document tracking system (DTS) - Sueno, Bernadette D. (School of Library and Information Studies, University of the Philippines Diliman, 2008)
DokuTrak, the University of the Philippines (UP) in-house developed Document Tracking System (DTS), was developed and implemented in 2001 to keep track of documents as they are processed within UP. Through DocuTrak, UP hopes to achieve administrative efficiency by computerizing manual administrative processes and procedures. Since its implementation however, neither an assessment nor any kind of follow-up has been made to check on the extent of its intended purpose.